2008
DOI: 10.1073/pnas.0706663105
|View full text |Cite
|
Sign up to set email alerts
|

T cell expression of MyD88 is required for resistance toToxoplasma gondii

Abstract: Resistance to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
100
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 47 publications
3
100
0
1
Order By: Relevance
“…Neutrophils participate in host response to T. gondii but play a limited role in survival of WT mice infected with the parasite (30-32). Instead, IFN-γ from NK and T cells predetermined susceptibility vs. resistance to the parasite (12,16,33). The dominance of neutrophils in IFN-γ production observed in T. gondii-infected TLR11 −/− mice prompted us to investigate their physiological importance.…”
Section: Percetage Of Ifn-+ Cellsmentioning
confidence: 99%
“…Neutrophils participate in host response to T. gondii but play a limited role in survival of WT mice infected with the parasite (30-32). Instead, IFN-γ from NK and T cells predetermined susceptibility vs. resistance to the parasite (12,16,33). The dominance of neutrophils in IFN-γ production observed in T. gondii-infected TLR11 −/− mice prompted us to investigate their physiological importance.…”
Section: Percetage Of Ifn-+ Cellsmentioning
confidence: 99%
“…TRAF6 is an E3 ubiquitin ligase and catalyzes K63 polyubiquitination of TAK1, which is required for IKK activation and is known to directly regulate ubiquitination and activation of AKT and mTORC1 as well as TGF-β (14)(15)(16)(17). Interestingly, CD4 or CD8 T cells lacking MyD88 exhibit reduced expansion and impaired survival in vivo (4)(5)(6)(7)(8)(9)(10). IRAK4 has been reported to be recruited to T cell lipid rafts, where it associates with ZAP70 and participates in protein kinase C activation (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies highlight an indispensable role for MyD88 signaling in primary T cells (4)(5)(6)(7)(8)(9)(10). The engagement of IL-1 receptor family members as well as TLRs (except TLR3) recruits the adapter protein MyD88, which in turn brings in an IL-1 receptor-associated kinase 4 (IRAK4), resulting in autophosphorylation.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not entirely clear how innate MyD88-dependent signaling regulates the activation of T-cell responses, it has been suggested that MyD88 expression in antigen-presenting cells (APCs), including dendritic cells (DCs), plays a key role in the activation of T-cell responses (2,15,27,39). Additionally, very recent studies have revealed an important role of MyD88 expression in T cells in regulating T-cell activation and pathogenesis in response to model antigens or parasites (11,26). However, it is not known whether MyD88 expression in T cells plays a similar role in the activation of T cells and regulation of pathogenesis in response to a virus.…”
mentioning
confidence: 99%